Human resource management and labour relations in the Indian industrial sector - Soumi Rai (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
This paper addresses gaps in research related to study and understanding of Human Resource Management in the context of Indian Automobile sector. The review is based on the available and published literature in peer reviewed journals of reputation and academic standing. A total of 138 papers were reviewed related to the general context of Human Resource Management practices. Of these, about 65 papers were found relevant and relating to understanding of HRM practices in India specifically in the context of the industrial sector. The timeline for literature review has been taken from 1970 - 2010, as it encompasses the period of industrialization in India, growth of HRM and major transition across Indian industrial sector post economic liberalization - 1991.
Keywords: 330